Pengaruh Harga dan Promosi Terhadap Minat Beli Pada Warunk Upnormal Samarinda - Andi Syarifuddin; Sugeng Hariadi; Bela Barus; Fauzi Amru (Politeknik Negeri Samarinda, 2021)
This study aims to determine the effect of price and promotion on Warunk Upnormal Samarinda. This research is categorized as survey research, where the instrument is a questionnaire. The sample in this study amounted to 100 people. The data analysis method was performed using multiple linear regression analysis using SPSS version 17.0 for windows. The results of this study indicate that partially price and promotion have a significant effect on purchase intention as well as simultaneously a significant effect on purchase intention at Warunk Upnormal. And from these three variables, it is known that promotion (X2) has a dominant effect compared to price (X1) on buying interest, this can be seen from the tcount where the tcount value for the promotion variable (X2) is 0.348 greater than the variable (X1) is 0.224 .